Pendekatan Hukum Terhadap Peredaran Gelap Narkotika Melalui Pendekatan Follow The Money - Sugeng Riyadi; Bismar Nasution; Madiasa Ablisar; Mahmud Mulyadi (Universitas Sumatera Utara, 2019)
Abstract. Generally, TPPU is carried out in the banking sector. The form is that the perpetrators of criminal acts try to hide or disguise the origin of assets that are the result of criminal acts in various ways so that the assets resulting from crime are difficult to trace by law enforcement officials so that they freely utilize these assets for both legal and illegal activities. Money laundering activities almost always involve banks because of the globalization of banks so that through the payment system, especially those that are electronic (electronic funds transfer), the proceeds of crime that are generally large amounts will flow or even move beyond national borders by utilizing the bank's confidential factors that are generally upheld high by banking. In this study, an example of a case that has permanent legal force will be raised, namely: Medan District Court Decision No. 1738/Pid.Sus/2016/PN.Mdn., Dated 28 June 2016 An. Defendant Abdul Jalil; and Decision of the Medan District Court No. 1995/Pid.Sus/2017/PN.Mdn., Dated November 1, 2017 An. Defendant Mursalin Alias ​​Salim. North Sumatra Police investigators conduct financial analysis of the accounts concerned. It turned out that a significant flow of funds was found to Abdul Jalil from the suspect An. Mursalin Alias ​​Salim. Efforts to strengthen the legal framework in the field of investigating money laundering is one of the efforts to prevent Indonesia from re-entering the NCCT's list issued by FATF. Investigation of money laundering by using the follow the money method is expected to increase the disclosure of cases of money laundering crimes that occur in Indonesia, especially regarding narcotics criminal action. Keywords : law enforcement; illicit narcotics circulation; and the follow the money approach.